Expression and characterization of thermotolerant lipase with broad pH profiles isolated from an Antarctic Pseudomonas sp strain AMS3 - Latip, Wahhida; Raja Abd Rahman, Raja Noor Zaliha; Thean, Adam Chor Leow; Mohd Shariff, Fairolniza; Mohamad Ali, Mohd Shukuri (PeerJ, 2016)
A gene encoding a thermotolerant lipase with broad pH was isolated from an Antarctic Pseudomonas strain AMS3. The recombinant lipase AMS3 was purified by single-step purification using affinity chromatography, yielding a purification fold of approximately 1.52 and a recovery of 50%. The molecular weight was approximately ∼60 kDa including the strep and affinity tags. Interestingly, the purified Antarctic AMS3 lipase exhibited broad temperature profile from 10-70 °C and stable over a broad pH range from 5.0 to pH 10.0. Various mono and divalent metal ions increased the activity of the AMS3 lipase, but Ni2+ decreased its activity. The purified lipase exhibited the highest activity in the presence of sunflower oil. In addition, the enzyme activity in 25% v/v solvents at 50 °C particularly to n-hexane, DMSO and methanol could be useful for catalysis reaction in organic solvent and at broad temperature.